2017
DOI: 10.1111/aogs.13231
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of continuous fetal monitoring – a mixed‐methods systematic review

Abstract: This review suggests that continuous fetal monitoring is accepted by women. However, it has also highlighted both the paucity and heterogeneity of current studies and suggests that further research should be conducted into women's experiences of continuous fetal monitoring before such devices can be used clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…This suggests that the technical performance of CFM using the Monica AN24 is consistent between study populations. As well as the quantitative measurements, the qualitative data obtained was consistent with a meta‐analysis of five published studies, identifying practical limitations of the device, high levels of satisfaction and maternal reassurance, but anxiety as to whether the FHR trace was normal.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This suggests that the technical performance of CFM using the Monica AN24 is consistent between study populations. As well as the quantitative measurements, the qualitative data obtained was consistent with a meta‐analysis of five published studies, identifying practical limitations of the device, high levels of satisfaction and maternal reassurance, but anxiety as to whether the FHR trace was normal.…”
Section: Discussionsupporting
confidence: 77%
“…Continuous fetal monitoring (CFM) describes technologies which can provide an objective view of fetal wellbeing and could be practically used over long periods of time. A systematic review of five studies including a total of 105 participants found a paucity of data about professionals’ and womens' experiences of CFM . This review identified four main themes: practical limitations of the device, negative emotions, positive perceptions and device implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Following the removal of duplicated articles, two reviewers with clinical experience (KT and AH) independently screened all titles and abstracts to determine their eligibility with regard to the inclusion and exclusion criteria, as stated previously; the articles were then categorised into one of three groups ('included', 'excluded' or 'uncertain'). The same definition for CFM was applied as mentioned in our previous systematic review [17]; only devices which can be used in the antenatal period, are non-invasive and those which can safely be potentially used for a sustained period of time were included in this review. Ultrasound-based technologies were excluded due to heating concerns associated with prolonged use [15].…”
Section: Plos Onementioning
confidence: 99%
“…Nonetheless, the experimental use of CFM devices has already prevented adverse outcomes in a number of cases, specifically using the Monica AN24 [50] and the FMAM [78]. In addition to this, as well as providing reassurance to women that their baby is being actively monitored [17], the use of a CFM device increases maternal awareness of fetal wellbeing [60]. This demonstrates the multiple benefits which can be achieved through the use of CFM in clinical practice, enabling timely identification of compromised fetuses which in turn could assist in the reduction of the stillbirth and neonatal mortality rates.…”
Section: Further Advancements Required In Cfmmentioning
confidence: 99%
See 1 more Smart Citation